Required Cauer network order for modelling of thermal transfer impedance. Issue 4 (1st February 2014) - Davidson, J.N.; Stone, D.A.; Foster, M.P.
Abstract : Impedance spectroscopy, a technique for analysing electroceramics, is applied to the two‐port form of the Cauer network which is commonly used as a thermal circuit analogue. The transfer impedance spectra of the Cauer network representations of a single material are presented as Nyquist plots for a range of network orders. The results demonstrate that a model with four or more resistor‐capacitor elements is required to accurately model a single material. The effect of taking a measurement at different points within a single material is then reported and four elements are similarly required between the heat source and the measurement. The existing modelling techniques, which often use only one element per material block, are shown to be especially inaccurate. By using these findings, a design engineer can produce a better thermal model of a complete system by making an informed compromise between the model's accuracy and complexity.